2016
DOI: 10.1007/s12351-016-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss-averse preferences in a two-echelon supply chain with yield risk and demand uncertainty

Abstract: We consider a one-period two-echelon supply chain composed of a lossaverse supplier with yield randomness and a loss-averse retailer with demand uncertainty. At the beginning of the selling season, the retailer orders from the supplier via the wholesale price contract, and then the supplier makes his production decision. We derive the loss-averse retailer's optimal ordering policy and the lossaverse supplier's optimal production policy under these conditions. In addition, we discuss the effect of loss aversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Some studies have examined the impact of low carbon preferences, as well as the methods and attitudes toward the fossil fuel used, on the production process [3][4][5]. Meanwhile, some research has constructed a demand function to systematically characterize the relationship between low carbon preferences, price, and product demand, and to investigate the impact of low carbon preferences on demand and price [6][7][8]. In addition, some studies have examined the influence of consumers' preferences for low carbon on supply chain coordination and optimization decisions from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the impact of low carbon preferences, as well as the methods and attitudes toward the fossil fuel used, on the production process [3][4][5]. Meanwhile, some research has constructed a demand function to systematically characterize the relationship between low carbon preferences, price, and product demand, and to investigate the impact of low carbon preferences on demand and price [6][7][8]. In addition, some studies have examined the influence of consumers' preferences for low carbon on supply chain coordination and optimization decisions from different perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…When both yield and demand are stochastic, Luo et al [20] study the supply chain coordination under three different contracts. Du et al [21] also consider the yield risk and demand uncertainty and study a supply chain with loss-averse supplier and retailer. Their optimal policies are obtained, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned above, the retailer's CVaR objective of utility is the expected utility when α = 0. In such a case, Q * reduces to the optimal order quantity that maximizes expected utility that is often studied in the supply chain models with loss-averse decision makers (e.g., [21][22][23]). Denote it by Q * 1 and then from (9) it satisfies…”
Section: Loss-averse Retailer's Ordering Policy Under the Combined Comentioning
confidence: 99%
“…Du et al investigated a two-echelon supply chain under the assumption that a supplier with yield randomness and a retailer with demand uncertainty are loss-averse. They found that the optimal order quantity of retailer with loss aversion may increase in wholesale price and decrease in retail price [42].…”
Section: Traditional Supply Chain Management With Loss-averse Membersmentioning
confidence: 99%